Representasi Gender dalam Praktik Ritual Barzanji: Analisis Komparatif Desa Rano Jaya dan Kelurahan Sabilambo - Anastasia Anastasia; Farid Wajdi; Zulfikar Putra (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the construction of gender roles in the Barzanji ritual in Rano Jaya Village and Sabilambo Subdistrict and to identify the socio cultural factors influencing their differences. The research employs a qualitative approach with a comparative study design, using in depth interviews, participant observation, and documentation as data collection techniques. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The findings reveal that the Barzanji practice in Rano Jaya Village represents a conservative complementary model characterized by male dominance in the public ritual sphere, whereas in Sabilambo Subdistrict an inclusive participatory model has developed since 2021, marked by the direct involvement of women in ritual recitation. These differences are influenced by local traditions, leadership dynamics, social openness, and the reinterpretation of religious values.